Eat for Immunity - Hartvig, Kirsten (London Duncan Baird, 2002)
"Eat for Immunity" combines the latest scientific research with authenticated traditional wisdom. The author shows how to prevent disease and fight infection using the most natural medicine there is - food
Include Color Illustration, Bibliography and Index
Keywords: Nutrition -- Immune system -- Immunity--Nutritional aspects